Predicting Elderly Depression Prevalence in Different Iranian Ethnicities and Associated Factors - Elahe Allahyari; Majid Keramati; Mohammadreza Kamali (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: There is currently a lack of consensus to estimate and compare depression proportion of elderly people in different Iranian ethnicities. Therefore, we examined the effect of ethnicity on elderly depression in the presence of other variables. Methods & Materials: During a cross-sectional study in 2017, seven Iranian ethnicities were considered as clusters, then a random sample was selected from each group of people over 60 years old. A total of 1477 participants were studied among which 675 were Fars, 298 Turk, 100 Kurds and Turkman, 99 Baloch and Arab, and 96 Lor. The subjects were asked to complete the Elderly Depression Inventory (GDS-15) and demographic checklist. Data were analyzed by SPSS v. 22 software in α=0.05 using linear regression analysis and ANOVA test. Results: The prevalence of depression was only about 50%. However, depression proportion of Baluch, Arab, Kurd and Lor elderlies with 81.8, 77.8, 62, and 59.4 percent was significantly high. Even, the prevalence of severe depression was 30% in Baluchis. Also, linear regression revealed that widowhood (P<0.001), retirement (P=0.022), house bound (P<0.001), and the increasing chronic illnesses (P<0.001), and income (P<0.001) were other variables influencing depression. Conclusion: The establishment of methods to decreasing elderly depression is necessary because of the high prevalence of depression among the elderly of different ethnicities, especially the Arab and Baluch ethnic groups.